A sketch of early days on the Purgatory - Taylor, Morris F. frey50 (Trinidad, CO Trinidad State Junior College, 1959)
A history of early life on the Purgatory River.
#12
Keywords: New Mexico - Northeastern New Mexico and Southeastern Colorado -- Purgatory River - Southeastern Colorado - History. -- Purgatory River - American history